L’ACCEPTABILITE SOCIALE DES PROJETS MINIERS EN ALGERIE: CAS DE AIN DEFLA ET BEJAIA - Azzeddine, Madani (European Scientific Journal, ESJ, 2015)
The social acceptability of mining projects in Algeria cases: Ain Defla and Bejaia The acceptability of some mining projects causes environmental problems, to the populations, despite the existence of laws to supervise the investment. In this article we try to explore all the required steps to obtain the mining permit. And we will see the content of the necessary studies for such authorization and the measures to be taken in such projects to have the opinion of the population in terms of the acceptability activity. Examples of mining projects having implementation and operational difficulties in Ain Defla, west of Alger, and Bejaia, east of Alger will be also presented in order to see the extent of the impact and measures taken to highlight the acceptability or rejection by the population. Finally solutions will be presented for each step in order to get the mining authorization, and to obtain acceptability and avoid refusal, which in some cases causes huge financial losses.